European Financial Linkages : A New Look At Imbalances. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
We document external investment positions among European Union countries at the start of the financial crisis through the creation of a new database comprising bilateral external financial asset and liabilities, excluding reserve assets and derivatives. While there are some gaps in the data, the overall coverage of reported bilateral net international investment positions (IIPs) appears satisfactory. The dataset provides a richer picture of financial linkages, enabling us to map the financing of Euro area imbalances. Creditor and debtor positions vis-a-vis the rest of the EU have tended to increase between 2000 and 2008, with capital flowing largely from wealthier to catching-up economies. This has in particular resulted in an increased interdependency among Euro Area economies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet